Thermal behaviour of the basic carbonates of lanthanum-europium - Luiz, J. M.; Matos, J. R.; Giolito, I.; Ionashiro, Massao [UNESP] (Elsevier B.V., 1995)
The basic carbonates of lanthanum with 10%, 20%, 50% and 80% of europium were prepared by precipitation from homogeneous solutions via the hydrolysis of urea, without the addition of an auxiliary anion, at two different temperatures. Elemental analysis, complexometric methods, X-ray diffraction patterns, solid state IR absorption, thermogravimetry/derivative thermogravimetry (TG/DTG) and differential thermal analysis (DTA) were used to characterise the compounds and study their thermal behaviour.
Keywords: Basic carbonate; Decomposition; Europium; Homogeneous precipitation; Lanthanum; TA